Nickel Nanopillar Arrays Electrodeposited on Silicon Substrates Using Porous Alumina Templates - Casagrande-Denardin, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Nickel nanopillar arrays were electrodeposited onto silicon substrates using porous alumina membranes as a template. The characterization of the samples was done by scanning electron microscopy, X-ray diffraction, and alternating force gradient magnetometry. Ni nanostructures were directly grown on Si by galvanostatic and potentiostatic electrodeposition techniques in three remarkable charge transfer configurations. Differences in the growth mechanisms of the nanopillars were observed, depending on the deposition method. A high correlation between the height of the nanopillars and the charge synthesis was observed irrespective of the electrochemical technique. The magnetization measurements demonstrated a main dependence with the height of the nanopillars. The synthesis of Ni nanosystems with a controllable aspect ratio provides an effective way to produce well-ordered networks for wide scientific applications. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.